2016
DOI: 10.4103/0366-6999.189923
|View full text |Cite
|
Sign up to set email alerts
|

Living near a Major Road in Beijing

Abstract: Background:The effects of near-road pollution on lung function in China have not been well studied. We aimed to investigate the effects of long-term exposure to traffic-related air pollution on lung function, airway inflammation, and respiratory symptoms.Methods:We enrolled 1003 residents aged 57.96 ± 8.99 years living in the Shichahai Community in Beijing. Distances between home addresses and the nearest major roads were measured to calculate home-road distance. We used the distance categories 1, 2, and 3, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The similar result was found by Bayer-Oglesby et al who concluded that living close to main streets or in a dense street network increases the risks for certain respiratory symptoms in adults [19]. In Beijing, long-term exposure to traffic-related air pollution in people who live near major roads was associated with a higher prevalence of chronic cough [20]. And finally, Hegseth et al found statistically significant associations between self-reported TRAP (traffic-related air pollution) exposure and respiratory symptoms in a large, random sample from a population living in an area with modest TRAP levels [21].…”
Section: Prevalence Of Respiratory Symptoms In the Proximity Of Road supporting
confidence: 79%
“…The similar result was found by Bayer-Oglesby et al who concluded that living close to main streets or in a dense street network increases the risks for certain respiratory symptoms in adults [19]. In Beijing, long-term exposure to traffic-related air pollution in people who live near major roads was associated with a higher prevalence of chronic cough [20]. And finally, Hegseth et al found statistically significant associations between self-reported TRAP (traffic-related air pollution) exposure and respiratory symptoms in a large, random sample from a population living in an area with modest TRAP levels [21].…”
Section: Prevalence Of Respiratory Symptoms In the Proximity Of Road supporting
confidence: 79%
“…Dwellings near roads or highways may also cause health problems related to air pollution. A recent study in Beijing suggests that longterm exposure to air pollution related to vehicle traffic on major roads in Beijing is associated with lower lung function, airway acidification, and a higher prevalence of chronic cough (Hu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the quantication of the blood and our additives could be determined by the Kjeldahl nitrogen method, organic elementary analysis, and the spectrophotometric method. [9][10][11] Furthermore, if two or more additives have been identied in one sample through proteomics, the relative abundance of protein groups could also be estimated by proteomics, 49 which is important for imitating ancient mortars. Thus, proteomic approaches could realize the qualitative and quantitative analysis of organic additives in the mortars, which is of signicant importance for unveiling old mortar technology and subsequently selecting suitable technological processes for restoration.…”
Section: Proteomics: An Informative Technique For the Identication Omentioning
confidence: 99%
“…8,9 Bloodstain tests in forensic science have been applied to examine short-period samples, and crude protein content could be determined by the Kjeldahl nitrogen method or organic elementary analysis. [9][10][11] However, these analytical methods cannot determine the precise origins of these binders, which should be important for understanding mortar technology as our and blood remarkably improve the anti-uting property and durability of the mortars. 12 On the other hand, the binders in various archaeological contexts have been well identied by micro-chemical analysis and staining methods, 13,14 spectroscopic techniques such as infrared spectroscopy and Raman spectroscopy, 15 starch grain analysis, 16 chromatographic methods including gas-phase and liquid-phase chromatography (coupled with mass spectrometry), [17][18][19] immunoassay techniques, 20 and recently developed proteomic methods.…”
Section: Introductionmentioning
confidence: 99%